COURSE SYLLABUS DESIGN: LANGUAGE TEACHING BASED SYLLABI TYPES - Fayzullayeva Muhayyo Raxmatillayeva,; Mirzakulova Feruza Mukhitdin kizi, (EPRA International Journal of Research and Development (IJRD), 2023)
It is well known that in the tertiary educational setting, instructors and students have and use a separate set of resources and documents. While instructors use registers, grading sheets, and reports to perform their professional duties, students use textbooks, library borrowings, and software databases to build knowledge. The syllabus is the single official document that serves as a contract between instructors and students. This article outlines course syllabus design and syllabi types that based on language teaching.